Convergence or Divergence? An Exploratory Study on Urban Malays and Indigenous People in Kuala Lumpur and Kuching - Shukri, Syaza Farhana Mohamad (Animo Repository, 2024)
Malaysia has been celebrated as a diverse nation since 1963. However, interethnic relations remain difficult as distrust appears to continue between the majority Malays and minority groups. This is the common narrative in Peninsular Malaysia. In East Malaysia, there is no clear ethnic majority population, which is also the case in Sarawak. Although the government has usually grouped together the Malays and indigenous people for nation-building purposes, it must be noted that the different backgrounds create a heterogeneous “majority” in Malaysia. This diversity may even explain the different views among the Malays in Kuala Lumpur and in Kuching, Sarawak regarding government policies. This study seeks to discover the perception of these two groups on issues including religion, ethnicity, law, politics, and education. Using elite interviews and a pilot survey, this study found that there seems to be a convergence relating to religious issues but divergence on other matters.